Ascending aortic perivascular adipose tissue inflammation associates with aortic valve disease. Issue 3 (September 2022) - Shi, Kailei; Anmin, Ren; Cai, Junfeng; Qi, Yiding; Han, Wanlin; Li, Mingxuan; Zhang, Guannan; Zhang, Shuyi; Fu, Lei; Han, Wenzheng; Guan, Shaofeng; Li, Jun; et al.
Abstract: Background: Ascending aortic perivascular adipose tissue (AA-PVAT) mainly comprises brown adipose tissue (BAT), originates from neural crest cells that derive from ectoderm, and plays important role in angiotensin II-induced vascular inflammation and remodeling in mice. However, the characterization and function of human AA-PVAT remains highly unclear. Methods: Patients with coronary artery disease (CAD) (n = 20) and aortic valve disease (AVD) (n = 23) who underwent cardiac surgery consented to take part in transcriptome and histological studies. Paired samples of AA-PVAT, epicardial adipose tissue (EAT), and subcutaneous adipose tissue (SAT) were obtained. RNA sequencing, histological analysis, quantitative reverse transcription polymerase chain reaction and western blot studies were performed on those samples. Results: Human AA-PVAT exhibited smaller adipocyte morphology and high expression of brown adipocyte marker. Transcriptome analysis revealed that AA-PVAT showed unique transcriptome characteristics compared with EAT and SAT. While comparing CAD and AVD patients, AA-PVAT exhibited a decreasing brown phenotype and higher inflammatory response in AVD patients. Gene ontology enrichment and Kyoto Encyclopedia of Genes and Genomes pathway analysis suggested that the differentially expressed genes in AA-PVAT between CAD and AVD patients were involved mainly in the processes of inflammation and metabolism regulation. Conclusions: Human AA-PVAT is a BAT-like adipose tissue with unique transcriptome characteristics, and exhibits a weakened brown phenotype and an enhanced inflammation response in AVD patients. Graphical abstract: Unlabelled Image Highlights: Human ascending aortic perivascular adipose tissue (AA-PVAT) is a brown adipose tissue-like adipose tissue. Human AA-PVAT carries unique transcriptome characteristics. Human AA-PVAT exhibits an enhanced inflammation response in aortic valve disease patients.